La Massorah del Libro di Rut (BHS) - Pazzini, M. (Liber Annuus, 2001)
Abstract The article offers an easy way to read and understand the notes, massorah parva (mp) and massorah magna (mm) of the book of Ruth in Biblia Hebraica Stuttgartensia (BHS). Starting with the printed biblical text the marginal notes of mp are explained at first. Afterwards references in the list of mm of the monograph published by G. Weil are examined.